The Implementation of Value-based Leadership in the State Islamic Higher Education Institutions - Ikhwanuddin Abdul Majid; Nik Md Saiful Azizi Nik Abdullah; Faisal Efendi; Muhammad Wildan Shohib; Adam Adesina Muhammad-Lawal (Jurnal Educative: Journal of Educational Studies, 2025)
This study aims to investigate the implementation of Value-Based Leadership (VBL) in selected Islamic higher educational institutions in North Sumatera, Indonesia. Despite the growing emphasis on leadership in Islamic higher education, empirical evidence on the perception and measurement of Value-Based Leadership in Indonesia remains limited. The research employs a quantitative approach, utilizing survey questionnaires to gather data from undergraduate students. The study's population comprises students from three State Islamic Universities: UIN Sumatera Utara, UIN Syahada Padangsidimpuan, and STAIN Madina, totaling 33,492 students. A stratified random sampling method was used to select a sample size of 380 respondents, ensuring representativeness across the institutions. The methodology involved descriptive analysis and Structural Equation Modeling (SEM), including Confirmatory Factor Analysis (CFA), to test the hypothesized model. Data screening was performed to identify missing data, outliers, and assess normality using skewness and kurtosis values. Key findings indicate that the highest perceived dimension of VBL among respondents is commitment emerged as the most prominent perceived dimension, followed by accountability, Integrity, and Sense of direction. The initial CFA model for VBL did not meet the Goodness-of-Fit (GoF) requirements. However, after re-specification through the removal of 5 items re-specification for improved fit the revised model demonstrated improved fit indices(230.470, df = 95, = 2.426, CFI = .986, RMSEA = .061, TLI = .982, GFI = .932. The convergent validity of the revised VBL model was confirmed, with AVE values 0.5 and CR values 0.7, supporting the validity and reliability of the VBL measurement model. This study contributes to understanding the perception and measurement of value-based leadership and offers a validated framework to guide research and leadership development in Islamic higher education.